STUDI AWAL EMPAT ISOLAT BAKTERI ANTAGONIS TERHADAP JAMUR Colletotrichum gloeosporioides - Elly Syafriani; Femy Riwany; Rahmi Handayani; Rahmi Kamelia; Istino Ferita; Fatchiyah Fatchiyah; Jamsari Jamsari (UPN VETERAN JAWA TIMUR, 2018)
Anthracnose disease on some important crops is caused by the Colletotrichum gloeosporioides. Because of this disease, many farmers were suffer a financial loss. The conventional way to solve this problem that taken by the farmers is synthetic fungicides application which has a negative impact on consumers and the environment. Another alternative to replace it is needed. Antagonistic microorganisms can be used to replace it then and to develop a biofungicide which is more safety for the consumers and the environment. Four isolates of antagonist bacteria to against C. gloeosporioides have been found, namely: UBCR_12, UBCR36, UBCF_01, and UBCF_13. They were being developed as the main material for the manufacture of biofungicide. As an initial step of it, some tests were conducted to identify and to obtain some information that related to the character of all the isolates. Gram staining and KOH test showed that UBCR_12, UBCR_36, and UBCF_01 were gram negative bacteria and UBCF_13 is gram positive bacteria. The four isolates were also showed rod morphological form. Oxidative-fermentative (OF) test showed that the four isolates are facultative anaerobic bacteria. The protease enzyme activity test showed that only 3 of 4 isolates can produced a protease enzyme with the highest clear zone index to the lowest, respectively are UBCR_12, UBCF_13, and UBCF_01. This information leads to choosing UBCR_12 for the molecular identification by the cloning 16S rRNA gene of it. The result showed that UBCR_12 is Serratia plymuthica.